Indigenous Learning Design for Teaching and Being: Implications for Educators Transitioning to Curriculum Embedded with Indigenous Ways of Knowing - Jungen, Philip (2016)
This project reflects upon my own personal experiences of teaching and learning, taking on an ethnographic lens as I begin to develop as an Ally. I use the process of planning for a new curriculum to re-think my teaching practice; both the known colonial influences as well as those I did not realize existed within me. I study the literature around Indigenous Ways of teaching science, relate it to my own experiences, and make classroom, school, and district recommendations. I move from the typical western perspective of learning and assessment to more traditional Indigenous Knowledge and Wisdom incorporating the power of story as a meaningful way of learning. The conclusion I draw is that there is much to be done to Indigenize our classrooms; curriculum change alone is not enough. True and lasting change will require ongoing and honest self-examination with a willingness to ask difficult questions and to become vulnerable to trusting that the answers have always been there. Graduate